2002
DOI: 10.1177/009127002401102786
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Blind, Placebo‐Controlled, Dose‐Response Study of the Effectiveness and Safety of Enalapril for Children with Hypertension

Abstract: Despite widespread use to treat childhood hypertension, enalapril has never been studied systematically to determine effectiveness, dose response, and safety in a pediatric population. This study was conducted prospectively in 110 hypertensive children ages 6 to 16 years in two sequential phases. The primary outcome variable for both phases of the study was trough (24-h postdose) sitting diastolic blood pressure. The primary objective of the first phase of the study was to determine whether enalapril lowered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(93 citation statements)
references
References 22 publications
3
89
0
1
Order By: Relevance
“…No long-term randomised trials have investigated the effect of kidney function and cardiovascular disease in children or adolescents with diabetes, and the consensus statements are based on extrapolations from adult studies. In short-term studies, ACE inhibitors have been effective and safe in non-diabetic hypertensive children [58,59], but long-term studies are lacking.…”
Section: Atherosclerosis Is Earlier and More Severe In Type 1 Diabetesmentioning
confidence: 99%
“…No long-term randomised trials have investigated the effect of kidney function and cardiovascular disease in children or adolescents with diabetes, and the consensus statements are based on extrapolations from adult studies. In short-term studies, ACE inhibitors have been effective and safe in non-diabetic hypertensive children [58,59], but long-term studies are lacking.…”
Section: Atherosclerosis Is Earlier and More Severe In Type 1 Diabetesmentioning
confidence: 99%
“…The studies enrolled children 6-16 years of age. The trials excluded children with severe hypertension (because of a placebo phase), low glomerular filtration rates (< 30 mL/min/1.73 m 2 ), electrolyte abnormalities, renal disease, and other substantive medical problems including clinically significant cardiac disease (5). The trial design (12) and dosing strata of each study are shown in Table 1.…”
mentioning
confidence: 99%
“…ACE inhibitors are generally well-tolerated, and the common adult side-effect of chronic cough was seen in less than 3% of a pediatric population treated with enalapril [39]. Given the beneficial effects on cardiac function and remodeling, these drugs are considered the drug of choice for patients with diminished cardiac function or left ventricular hypertrophy.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%